2011
DOI: 10.2495/rm110251
|View full text |Cite
|
Sign up to set email alerts
|

Impact of selective logging and an intensive line planting system on runoff and soil erosion in a tropical Indonesian rainforest

Abstract: Tropical forest management with selective logging and an intensive line planting system are expected to change the hydrological cycle. This study was conducted in a natural tropical rainforest of Central Kalimantan, Indonesia. Direct runoff and soil erosion were studied at three small catchment plots, a virgin forest catchment, a 1-year-old line plantation (2008 catchment) and a 10-year-old line plantation (1999 catchment). Direct runoff in the virgin forest catchment was 13.5% of precipitation. In the 1999 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The number of rainy days varies from 95 to 112 days, and the mean temperature is 30-33°C at noon and 22-28°C at night [25]. Based on Forest Type Classifi cation map, the study site was classifi ed located in the tropical lowland rainforest with similar forest vegetation characteristics in structure and species distribution.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The number of rainy days varies from 95 to 112 days, and the mean temperature is 30-33°C at noon and 22-28°C at night [25]. Based on Forest Type Classifi cation map, the study site was classifi ed located in the tropical lowland rainforest with similar forest vegetation characteristics in structure and species distribution.…”
Section: Study Sitementioning
confidence: 99%
“…The main activities covered by the IFMS are selective logging and intensive line planting. Several studies have investigated the rainfall-runoff-erosion in Kalimantan, Indonesia [18,[22][23][24][25]. Research concerning the IFMS in tropical Indonesian rainforest is still limited [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements then focus on the differences in hydrological response between the control and treatment catchment (Fohrer et al, 2005). Suryatmojo et al (2011) used this approach to assess the impacts of different forest harvesting strategies (i.e. selective logging) on the streamflow characteristics in Central Kalimantan, Indonesia, and found that applications of different forest harvesting strategies resulted in different hydrological responses (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…comparison studies between control catchments and catchments under treatment) (e.g. Bosch and Hewlett, 1982;Brown et al, 2005;Suryatmojo et al, 2011;Zhao et al, 2012), a single model framework (e.g. Niehoff et al, 2002;Ashagrie et al, 2006;Menzel et al, 2009;Suarez et al, 2013) and multiple models (ensemble modeling) (e.g.…”
Section: Introductionmentioning
confidence: 99%